Money Matters: From the Power of Capital to Political Power in the City of Tasikmalaya, Indonesia - Mohamad Ali Andrias; Leo Agustino; Muhammad Ashsubli; Dina Fitriani Wulandari (Universitas Muhammadiyah Tangerang, 2026)
Since the 1998 Reformation, Indonesian politics has experienced major institutional transformation toward electoral democracy. One crucial change is the direct election of regional heads, including mayors, who were previously appointed by governors with central government approval. However, this shift also brings new challenges. This article examines the case of PT. Mayasari Bakti Utama (MBU) as an example of a capital-based political dynasty. The family owning this large transportation company has utilized its economic resources to build political power in Tasikmalaya, Indonesia. The study aims to explain how both informal actors (such as kyai) and formal actors (political party elites) are mobilized for family political interests. Using field observations, in-depth interviews, focus group discussions, and library research, this study finds that, first, the MBU family employs kyai networks to build legitimacy among Tasikmalaya's religious population. The charisma of the kyai shapes voter behavior in favor of the MBU family. Second, political elites use their positions to support the family's electoral ambitions. Third, unequal capital distribution enables the MBU family to